Sound ideas : music, machines, and experience - Evens, Aden (Theory out of bounds ;, 2005)
Aden Evens provides an acute consideration of how music becomes sensible, advancing original variations on the themes of creativity and habit, analog and digital technologies, and improvisation and repetition. Sound Ideas reinvents the philosophy of music in a way that encompasses traditional aspects of musicology, avant-garde explorations of music's relation to noise and silence, and the consequences of digitization.